Local earthquakes on the Ukrainian Shield - Yu. A. Andrushchenko; V. V. Kutas; A. V. Kendzera; V. D. Omelchenko; I. A. Kalitova (Геофизический журнал, 2013)
The data on local earthquakes with 2,0-4,5 magnitudes in the western and central part of the Ukrainian Shield in 2005-2013 have been presented. The nature of appearance of the earthquakes with magnitude 3,5-4,5 within the Krivoy Rog iron ore structure has been analyzed. Information of the number and magnitude of industrial explosions performed in the open pits and mines in 2011-2012 has been given.